Knowledge and practice of under-five care takers on the prevention of malnutrition at the uth - Kapema, Malamula (Lusaka: University of Zambia , School of Medicine, 2011)
The study was undertaken at the UTH University Teaching Hospital to in the malnutrition ward A07. The objective was to determine the knowledge and practices of caretakers of under five children admitted with malnutrition at the UTH.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Malnutrition --Zambia.; Child Nutritional Status --in infancy & childhood; Child Nutrition Disorders --therapy.